Gotong royong (cooperation) transformation of rural communities in Jambi Province, Indonesia - Rosyani Rosyani; Fuad Muchlis; Dompak Napitupulu; Heiko Faust (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
One nowadays un denied phenomena is that society changed. Jambi Province rural community has also changed toward modernization. The main goal of this research is to analyze factors effect gotong royong (cooperation) transformation in Jambi Province rural communities based on its remoteness from urban area. The research analysis used in this research is the Delphi method. Research found that there has been a change in the value of gotong royong in Jambi Province. It was also found that there are differences in changes in rural locations that are close to city and that are far from city. Some factors effecting the transformation are information technology, household income and accessibility while some factors that keeps gotong royong alive are family, harmony and help. The strategy to keep gotong royong value remain solid in Jambi Province’s villages should be to wisely accept global technology, income increases and better accessibility while still maintain the social capital strength.